Den arabiske roman fra 1980’erne og frem - Guth, Stephan (Passage - Tidsskrift for litteratur og kritik, 2009)
Stephan Guth: “The Arabic Novel since the 1980s” The study examines some recurrent motifs in Arabic novels from the 1980s until the early 2000s in the light of an analytical method that assigns “postmodern” features their place in a trinary structure of meaning. Faced with the destruction of their “houses”, the heroes start to “dig” in the ruins and, later in the period, begin to discover “treasures” that seem to have survived undamaged: An alternative approach in a time where the term “postmodernism” has come under attack as being too Eurocentrist.